Alexandre Vattemare papers - Vattemare, Alexandre, 1796-1864.
Report on metric weights and measures, letter (1853 December 12) written by Vattemare to Hannibal Hamlin relating to the report, and chart of metrical measures and weights.
French actor and ventriloquist who became an advocate for cultural exchange between the United States and France. Full name: Nicolas-Marie-Alexandre Vattemare.
Collection material in English, with French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hamlin, Hannibal, -- 1809-1891 -- Correspondence; Cultural relations; Metric system; Weights and measures; France -- Relations -- United States; United States -- Relations -- France; Actors; Ventriloquists